A case study exploring the level of awareness of NCP Chlorchem's staff of environmental costs associated with hazardous waste - Tlhapane, Keatlaretse Kefilwe (Rhodes University, Faculty of Commerce, Rhodes Business School, 2014)
[Integrative executive summary] NCP Chlorchem (Pty) Ltd manufactures and distributes Chlor alkali products such as chlorine, hydrochloric acid, caustic soda flakes, etc. and in the process generates both hazardous and general waste. Following changes in South African waste management legislation in 2011, the organisation's waste service provider had to increase the costs associated with the handling of site's hazardous waste. Top management of NCP Chlorchem (Pty) Ltd requested a meeting with the waste service provider in order to establish the reasons behind the price increase. In that meeting, which the researcher attended, the waste service provider explained the changes in waste legislation and how it was going to impact on their business. Top management understood the reasons behind the price increase; however, they requested the waste service provider to review the price increase. The waste service provider gave the top management of NCP Chlorchem (Pty) Ltd assurance that they were going to discuss the price reduction request with their own senior management and would provide feedback. The researcher did not participate in the feedback meetings; however, to this day, NCP Chlorchem (Pty) Ltd still uses the services of the same waste service provider. The effect the escalating annual waste handling costs has had on NCP Chlorchem (Pty) Ltd's management team led to the study. Environmental impacts have costs that directly impact on company's bottom line, such as the costs associated with the generation of waste. Although environmental costs are only one of the many costs incurred by businesses, they deserve management's attention. According to Jasch (2003), there is an apparent lack of awareness and understanding of the magnitude of the environmental costs generated by organisations, and many opportunities for cost savings through good environmental management are lost. However, using a relatively new tool in environmental management, that is, environmental management accounting (EMA), management would ensure that relevant and significant environmental costs are considered when making business decisions (Jasch, 2003). The main purpose of the thesis is to explore the level of awareness of environmental costs associated with hazardous waste within NCP Chlorchem (Pty) Ltd. In order to carry out the study, literature about environmental and cost accounting as well as literature on waste management was reviewed. Questionnaires were distributed to staff members, and meetings were held with different senior personnel. This case study seeks to answer the following questions: What is NCP Chlorchem (Pty) Ltd's staff members' level of understanding of waste management? What is the level of awareness of NCP Chlorchem (Pty) Ltd's staff of environmental costs with regard to the generation, handling, transportation and disposal of hazardous waste? How can the current traditional accounting within the organisation be integrated with environmental management accounting? The findings of the first research objective revealed that staff members knew the site's waste streams as per the South African legal definition of waste and as identified in the site's environmental management system documentation. The conceptual approach to waste management is underpinned by the waste hierarchy. The respondents support the waste hierarchy in its approach to waste management, which is prevention of waste, reduction, reuse, recycle and safe disposal of waste as the last resort. Lack of awareness of environmental management, among other things, was cited as the cause of waste. In addition to that, the respondents believe the waste hierarchy can be achieved by employing recycling facilities, following procedures and by carrying out environmental awareness campaigns. Improving process design and control and including changes in raw material was cited, among other things, as the respondents' perception on how waste can be reduced. The findings of the respondents' understanding of waste hierarchy revealed that staff members understood waste management. The respondents cited the impacts of waste on the business as financial impact on the business, impact on their bonuses, and possible loss of business. In relation to the second research objective, it was found that staff members knew the hazardous waste streams and identified amongst other waste, sludge and chlorine emissions as NCP Chlorchem (Pty) Ltd's hazardous waste. However, with regard to environmental management accounting data, an average of 55.1% of respondents were not familiar with the physical and monetary components of EMA. An average of 19.6% of respondents who were aware of EMA might have been senior personnel. It could further be established that those who were familiar with EMA information were actually working with the data, either for reporting purposes, or for employing waste minimisation strategies, as well as awareness purposes, to their juniors. On average, 80% of the respondents perceived the production department as the area within site that has the EMA information.
Keywords: Chlorchem (Firm); Environmental auditing -- South Africa -- Ekurhuleni; Hazardous wastes -- South Africa -- Ekurhuleni; Hazardous wastes -- Environmental aspects; Hazardous wastes -- Economic aspects; Hazardous wastes -- Management; Hazardous wastes -- Law and legislation -- South Africa